Everyday geographies of belonging: Syrian refugee experiences in the Northern Netherlands - Huizinga, Rik P.; van Hoven, Bettina (Geoforum, 2018)
•Refugee belonging in the Northern Netherlands is multifaceted, nuanced and relational.•Belonging emerges in everyday places through social encounters and interaction with others.•Different time geographies affect interethnic contact between refugees and locals.•Places of transnationalism allow refugees to establish ‘new places’ of belonging. The Dutch government currently underemphasises the interaction between refugees and place in the context of refugee spatial dispersal policy. This paper seeks a more detailed understanding of refugee integration by looking at opportunities for, and obstacles to, belonging within the ethnically homogeneous context of the Northern Netherlands. We draw on in-depth and walking interviews to provide a rich illustration of the daily routines and activities of ten Syrian male refugees in and around their residential neighbourhoods. Our findings highlight that a sense of belonging is grounded and embodied in space and place, and emphasise the role of everyday neighbourhood places as sites where refugee (non-)belonging emerges through social (non-)encounters and (non-)interaction with others. Daily life in transitory neighbourhood spaces provides opportunities for refugees to develop and maintain social relationships, asserting their presence and belonging in neighbourhood life. However, at the same time, refugees are demarcated as others because the different time geographies of refugees and existing residents form barriers to establishing nodes of encounter. Their otherness is further accentuated as potential places of encounter are often legally or economically inaccessible. Due to these experiences, or at least in part, refugees develop ‘new places’ built around shared memories, stories and food practices from their home country. Consequently, we argue for a more constructive understanding of migrant communities and suggest allowing multiple spaces of refugee belonging. Our study shows that achieving belonging is a multifaceted, nuanced and relational process, and one that is undervalued in the context of refugee dispersal in the Netherlands.